Circulating Mycobacterium tuberculosis DosR latency antigen-specific, polyfunctional, regulatory IL10(+) Th17 CD4 T-cells differentiate latent from active tuberculosis - Rakshit, Srabanti (Sci Rep, 2017)
The functional heterogeneity of T cell responses to diverse antigens expressed at different stages of Mycobacterium tuberculosis (Mtb) infection, in particular early secreted versus dormancy related latency antigens expressed later, that distinguish subjects with latent (LTBI), pulmonary (PTB) or extrapulmonary (EPTB) tuberculosis remains unclear. Here we show blood central memory CD4 T-cell responses specific to Mtb dormancy related (DosR) latency, but not classical immunodominant secretory antigens, to clearly differentiate LTBI from EPTB and PTB. The polyfunctionality score integrating up to 31 DosR-specific CD4 T-cell functional profiles was significantly higher in LTBI than EPTB or PTB subjects. Further analysis of 256 DosR-specific T-cell functional profiles identified regulatory IL10 (+) Th17 cells (IL10(+)IL17A(+)IL17F(+)IL22(+)) to be significantly enriched in LTBI; in contrast to pro-inflammatory Th17 cells (IFNγ(+)IL17A(+)/IL10(−)) in the blood and lung of EPTB and PTB subjects respectively. A blood polyfunctional, Mtb DosR latency antigen specific, regulatory, central memory response is therefore a novel functional component of T-cell immunity in latent TB and potential correlate of protection.